1987
DOI: 10.1021/bi00376a023
|View full text |Cite
|
Sign up to set email alerts
|

Iron(III) clusters bound to horse spleen apoferritin: an x-ray absorption and Moessbauer spectroscopy study that shows that iron nuclei can form on the protein

Abstract: Ferritin is a complex of a hollow, spherical protein and a hydrous, ferric oxide core of less than or equal to 4500 iron atoms inside the apoprotein coat; the apoprotein has multiple (ca. 12) binding sites for monoatomic metal ions, e.g., Fe(II), V(IV), Tb(III), that may be important in the initiation of iron core formation. In an earlier study we observed that the oxidation of Fe(II) vacated some, but not all, of the metal-binding sites, suggesting migration of some Fe during oxidation, possibly to form nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
43
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 33 publications
9
43
0
Order By: Relevance
“…This is also consistent with the relatively high occupancies of the Fe-O shells and the Fe-O distances which are a little bit too short to be all Fe-O(carboxylate) distances when compared with the distance of 2.01 Å given in the metalloprotein crystal structure survey [31]. The observation of polynuclear Fe-O cluster formation upon addition of Fe(II) ions to apoferritin is consistent with literature results [11,41].…”
Section: Iron-loaded Rhuhf Variantssupporting
confidence: 90%
“…This is also consistent with the relatively high occupancies of the Fe-O shells and the Fe-O distances which are a little bit too short to be all Fe-O(carboxylate) distances when compared with the distance of 2.01 Å given in the metalloprotein crystal structure survey [31]. The observation of polynuclear Fe-O cluster formation upon addition of Fe(II) ions to apoferritin is consistent with literature results [11,41].…”
Section: Iron-loaded Rhuhf Variantssupporting
confidence: 90%
“…Unfortunately, no data on iron binding of apobacterioferritin have been reported so far. However, Mossbauer spectra of iron binding to apo-ferritin exhibit parameters similar to holo-ferritin at an iron/protein ratio as low as 0.8 Fe atom/subunit [36]. In our case an iron/protein ratio of about 13 Fe atoms/subunit was found, which would yield the characteristic Mossbauer spectrum of ferric holo-bacterioferritin.…”
Section: Discussionsupporting
confidence: 41%
“…In recent in vitro Mossbauer studies on the redox properties of ferritin [37,38], bacterioferritin [35] and of iron binding to apo-ferritin [36], Mossbauer parameters of Fez+ species were reported which resemble the Fe2 + component presented here. Therefore, it might be assumed that the ferrous species observed in our spectra arises from a ferrous form of bacterioferritin.…”
Section: Discussionmentioning
confidence: 58%
“…It was suggested that the acidic side chains play a critical role in Fe(III) nucleation on the cavity surface (14,65,66). In contrast, Bou-Abdallah et al (67) demonstrated that the core formation rate was not affected by deletion of the inner glutamate residues (Glu 64 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The H chain possesses the ferroxidase site (15,16), which is positioned inside the 4-helix bundle of each subunit and is responsible for oxidation of ferrous iron atoms to produce the -oxo-bridged Fe(III) species. The ferroxidase site is composed of six residues: Glu 27 , Tyr 34 , Glu 62 , His 65 , Glu 107 , and Gln 141 , which coordinate with metal ions directly or indirectly. Crystallographic analyses of ferritin in vertebrates (4,5,17), insects (18), and bacteria (7,19) revealed an extremely high degree of similarity among the structures of these ferroxidase centers.…”
mentioning
confidence: 99%